Pengaruh Kecemasan Pasutri Yang Belum Dikaruniai Keturunan Terhadap Interaksi Sosial Di Jorong Simpang Hilir Kec. Simpang Alahan Mati, Kab. Pasaman - Natasya Putri; Linda Yarni (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is motivated by the phenomenon of anxiety felt by married couples which arise because they have not been blessed with offspring, feeling embarrassed because they have not been blessed with offspring and being criticized by the surrounding community, the perception that married couples who have not been blessed with offspring have certain diseases and also the perception of the extinction of the family tree because not blessed with offspring. The aim of this research is to determine the influence of anxiety of married couples who have not been blessed with offspring on social interaction and to find out how much influence the anxiety of married couples who have not been blessed with offspring has on social interaction in Jorong Simpang Hilir District. Simpang Alahan Mati, Kab. Pasaman. This research uses quantitative research that is regression in nature by interpreting actual events obtained with the results through numbers. The population in this study was 40 husband and wife who had not yet had children in Jorong Simpang Hilir District. Simpang Alahan Mati, Kab. Pasaman. The samples taken in this research were the entire population using a total sampling technique of 40 people. Data collection used a questionnaire research instrument with a closed questionnaire type and data analysis techniques using Microsoft Excel and SPSS 24.0 for Windows. Based on the research results, it was obtained that rcount was 0.231 > rtable 0.152 from df= 38, at a significance level of 0.05. So it can be concluded that there is a significant influence between the anxiety of married couples who have not yet been blessed with children on social interactions in Jorong Simpang Hilir District. Simpang Alahan Mati, Kab. Pasaman. Which means Ha is accepted and Ho is rejected. Based on the results of the coefficient of determination, the result was = 5.3%. Based on this value, it can be interpreted that married couples' anxiety influences social interactions by 5.3%, while 94.7% is influenced by other factors not included in this study.